Recent results from the study of West Bohemian uranium miners exposed to radon and its progeny. - Tomásek, L; Darby, S (1995)
A brief description is given of the study of West Bohemian uranium miners, and recent and ongoing efforts to improve the quality of the data are summarized. Three recent analyses of the data from the cohort have led to rather different estimates of the excess relative risk of mortality from lung cancer per working-level month. The reasons for these different estimates are described, and it is concluded that estimates of lung cancer risk are strongly influenced by the quality of the exposure estimates, especially by the omission of some exposures accumulated during employment at other uranium mines, following the closure of most of the shafts at the original two mines. The most recent analysis has shown that, in common with other cohorts of radon-exposed miners, the excess relative risk of lung cancer per working-level month is modified by age and time since exposure. An inverse effect of exposure rate was also demonstrated, but it affected only men at very high concentrations and appears to be related to the time pattern of exposure. In addition, the risk was found to differ between the two main mines, possibly due to the influence of arsenic in the dust of the mines.